IMPLEMENTATION OF KNOWLEDGE MANAGEMENT SYSTEM IN BUSINESS PROCESSES MANAGEMENT OF 3PL-PROVIDERS - N. Nosyrev (Вестник университета)
The paper deals with the theoretical aspects of knowledge management in organizations. The emphasis on the relevance of the introduction of knowledge management system in the management of logistics service providers is done. The results of the developed procedure for the introduction of the knowledge management system in the management of business processes in organizations of 3PL (Third party logistic) providers, as well as the classification of knowledge about processes in 3PL organizations, are presented. On the basis of theoretical studies, the main stages of knowledge integration into business process management in 3PL providers have been determined.